Customizing intense interval exercise training prescription using the “frequency, intensity, time, and type of exercise” (FITT) principle - Stavrinou, Pinelopi S.; Astorino, Todd A.; Giannaki, Christoforos D.; Aphamis, George; Bogdanis, Gregory C. (Frontiers in Physiology, 2025)
Intense interval exercise training induces various physiological and metabolic adaptations related to performance and health. For designing a program, the F.I.T.T. principle, referring to frequency, intensity, time, and type of exercise, can be used to manipulate the level of physiological stress in the body, leading to various adaptations. Modifying these four parameters results in a wide range of interval protocols that are safe and effective for different populations including athletes and individuals with chronic diseases. In this review, we present how the manipulation of the F.I.T.T. components can alter the acute and chronic cardiorespiratory, metabolic, perceptual, and affective responses and adaptations to intense interval exercise training. From this evidence, it appears that the duration of the exercise bout and recovery interval are critical parameters for the manipulation of almost all acute responses, enabling periodization of intense interval exercise training, and promoting optimal adaptations and exercise adherence. In addition, a considerable level of adaptations may be achieved with training frequencies as low as once or twice per week and with lower than maximal intensities, adding to the feasibility of this exercise mode. Overall, by varying these parameters, the design of an intense interval exercise training program can be tailored according to the needs and abilities of each individual, and an optimized training prescription may be achieved.